Evidence That ITPR2-Mediated Intracellular Calcium Release in Oligodendrocytes Regulates the Development of Carbonic Anhydrase II + Type I/II Oligodendrocytes and the Sizes of Myelin Fibers - Mei, Ruyi; Huang, Linyu; Wu, Mengyuan; Jiang, Chunxia; Yang, Aifen; Tao, Huaping; Zheng, Kang; Yang, Junlin; Shen, Wanhua; Chen, Xianjun; Zhao, Xiaofeng; Qiu, Mengsheng (Frontiers in Cellular Neuroscience, 2021)
Myelination of neuronal axons in the central nervous system (CNS) by oligodendrocytes (OLs) enables rapid saltatory conductance and axonal integrity, which are crucial for normal brain functioning. Previous studies suggested that different subtypes of oligodendrocytes in the CNS form different types of myelin determined by the diameter of axons in the unit. However, the molecular mechanisms underlying the developmental association of different types of oligodendrocytes with different fiber sizes remain elusive. In the present study, we present the evidence that the intracellular Ca2+ release channel associated receptor (Itpr2) contributes to this developmental process. During early development, Itpr2 is selectively up-regulated in oligodendrocytes coinciding with the initiation of myelination. Functional analyses in both conventional and conditional Itpr2 mutant mice revealed that Itpr2 deficiency causes a developmental delay of OLs differentiation, resulting in an increased percentage of CAII+ type I/II OLs which prefer to myelinate small-diameter axons in the CNS. The increased percentage of small caliber myelinated axons leads to an abnormal compound action potentials (CAP) in the optic nerves. Together, these findings revealed a previously unrecognized role for Itpr2-mediated calcium signaling in regulating the development of different types of oligodendrocytes.